If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + -7 = 5y + 17 Reorder the terms: -7 + -3y = 5y + 17 Reorder the terms: -7 + -3y = 17 + 5y Solving -7 + -3y = 17 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -7 + -3y + -5y = 17 + 5y + -5y Combine like terms: -3y + -5y = -8y -7 + -8y = 17 + 5y + -5y Combine like terms: 5y + -5y = 0 -7 + -8y = 17 + 0 -7 + -8y = 17 Add '7' to each side of the equation. -7 + 7 + -8y = 17 + 7 Combine like terms: -7 + 7 = 0 0 + -8y = 17 + 7 -8y = 17 + 7 Combine like terms: 17 + 7 = 24 -8y = 24 Divide each side by '-8'. y = -3 Simplifying y = -3
| T-2.3=6.7 | | 7x+11=-19+3x | | 3m^2-4m-8=0 | | 10n-12=-4 | | 653.10=42(x+2.55) | | 2(-7r+3)=-4(6+8r)-6r | | 2m-m/7=6+m | | y=2x+1/3 | | 5x=3x-(x-18) | | 5(x-5)-5=-30 | | 3x^2=237 | | 0.6x-0.3(60+x)=-15(60) | | y+1(9+24)+-28=21 | | x-3(2x)=5 | | m^2+4m-8=0 | | 0.6-0.3(60+x)=-0.15(60) | | 6a-4a+5a=8-2a | | 4a^2-4ap+p^2= | | 0.6x-03(60+x)=-0.15(60) | | 6z-8=7z-1 | | 4x-x=5 | | 31+4+-T=40 | | 4m^2-48=0 | | 6a+3a-5=7a+23 | | 9s^2+12st+4t^2= | | (2)(4)-(6-3)/-3 | | 6am+3a-5=7a-23 | | 5.5z=-93.5 | | 4w^3+12w-9= | | 3y+2/2 | | -10c=-30 | | 0=3t^2-12t |